Psychometric properties and construct validity of the Parkinson’s Disease-Cognitive Rating Scale (PD-CRS) in Colombia - Clavijo-Moran, Hugo Juan Camilo; Álvarez-García, Daniela; Pinilla-Monsalve, Gabriel D.; Muñoz-Ospina, Beatriz; Orozco, Jorge (Frontiers in Psychology, 2022)
Background: Cognitive impairment is frequent amongst people living with Parkinson’s disease: up to 40% of patients exhibit symptoms of mild cognitive impairment and 25% meet the criteria for dementia. PD-CRS is one of the recommended scales by the Movement Disorders Society Task Force (MDS-TF) for level 1 screening of dementia. However, its psychometric properties have not been studied in the Colombian population. Methods: A cross-sectional study was conducted on 100 patients with Parkinson’s disease diagnosed by a movement disorders neurologist. Patients were evaluated with PD-CRS and MoCA. Principal component analysis was conducted, and then confirmatory factor analysis was implemented through the maximum-likelihood method. Internal consistency was evaluated using Cronbach α. Convergent and divergent validity were also calculated and concurrent validity with the MoCA was assessed. Results: 62% were males. Their median age was 68 years (IQR 57-74) and the median disease duration was 4 years (IQR 2-9). 77% were classified in early stages (Hoehn and Yahr ≤2) while the MDS-UPDRS part III score was 25 (IQR 15.5-38). In the principal component factor analysis, the pattern matrix unveiled a mnesic and a non-mnesic domain. Confirmatory factor analysis showed similar explanatory capacity (λ≥0.50) for items other than naming (λ=0.34). Cronbach’s α for the full 9-items instrument was 0.74. MoCA and PD-CRS total scores were correlated (ρ=0.71, p=0.000). Assuming a cut-off score of 62 points, there is an agreement of 89% with the definition of dementia by MoCA for Colombia (κ=0.59; p=0.000). Conclusions: PD-CRS has acceptable psychometric properties for the Colombian population and has significant correlation and agreement with a validated scale (MoCA).